2014
DOI: 10.1007/s00204-014-1319-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxidatively damaged guanosine in white blood cells and in urine of welders: associations with exposure to welding fumes and body iron stores

Abstract: The International Agency for Research on Cancer considers the carcinogenicity of welding fume of priority for re-evaluation. Genotoxic effects in experimental animals are still inconclusive. Here, we investigated the association of personal exposure to metals in respirable welding fumes during a working shift with oxidatively damaged guanosine in DNA of white blood cells (WBC) and in postshift urine samples from 238 welders. Medians of 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodGuo) were 2.35/106 dGuo in DNA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Consistent with our study, Nuernberg et al (2008) reported a significant increase in urinary 8-OHdG after 6 h of exposure to welding fumes in welders who worked as boilermakers ( n = 41). Similar results were obtained in the studies with 20 volunteers from local welding apprentice schools in Switzerland (Graczyk et al, 2016) and 238 welders in Germany (Pesch et al, 2015). Also, 8-OHdG levels were found to be higher in animals exposed to welding fumes (Krishnaraj et al, 2017; Yu et al, 2004).…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with our study, Nuernberg et al (2008) reported a significant increase in urinary 8-OHdG after 6 h of exposure to welding fumes in welders who worked as boilermakers ( n = 41). Similar results were obtained in the studies with 20 volunteers from local welding apprentice schools in Switzerland (Graczyk et al, 2016) and 238 welders in Germany (Pesch et al, 2015). Also, 8-OHdG levels were found to be higher in animals exposed to welding fumes (Krishnaraj et al, 2017; Yu et al, 2004).…”
Section: Discussionsupporting
confidence: 85%
“…H 2 O 2 can also diffuse rapidly and readily between and within cells, which enhances the cascade of systemic oxidant response [ 4 , 25 ]. In regards to the significant increase witnessed for 8-OHdG, welding fume PM metal components are known to promote the oxidation of nucleobases and the intracellular nucleotide pool [ 33 , 52 ]. The mechanism by which the metal component of welding fumes can cause oxidative stress may act not only by directly producing radicals but also through signalling pathways, such as via mitogen-activated protein kinases (MAPK) and NF-kB, to generate pro-inflammatory mediators that results in a state of inflammation [ 15 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urinary Cr, Ni, and Cd levels were positively correlated with the 8-OHdG concentration. The geometric mean 8-OHdG concentration (5.02 μg/g creatinine) in welders in this study was higher than that in gas metal arc welders working with stainless steel, flux-cored arc welders working with mild steel, tungsten inert gas welders, and welders wearing a powered air-purifying respirator in an earlier study (median = 3.79–4.41 μg/g creatinine) [29], as well as welders in another study (median = 3.97 μg/L) [30]. Compared with other occupational metal exposure, the median urinary 8-OHdG concentration was considerably higher in workers exposed to hexavalent Cr electroplating (median = 13.65 μg/g creatinine) than in welders in our study [31]; in another study involving workers exposed to hexavalent Cr electroplating, the urinary 8-OHdG concentration was higher than that in our study (mean = 20.73 μg/L) [32].…”
Section: Discussionmentioning
confidence: 54%